Strategi Memberi Apresiasi Kepada Tokoh-tokoh di Desa - A Sofwan F Alqap; Afdhal K Mainil; Eko Sumartono (Dharmakayana, 2024)
Stakeholder involvement is the key to the strength of the institution. A village institution with many programs that are the focus of many parties become the center of attention of the entire community, the skill of head of the village (HOV) in appreciating figures who are interested in a program is the key to the success of the program runs and they appreciate the leadership of HOV. An affair has two types of figures, traditional (known before) and emerging (unknown before). As a result of information searching does not cover both it may become an obstacle for a program to be implemented perfectly. Either a strategy of searching covering information or appreciation strategy to both figures is discussed.